Analysis of radioactive iodine treatment in patients with hyperthyroidism: A narrative review - Oliveira, Anna Ligia de; Gebara, Julia Peres; Costa, Laís Borges; Costa , Livia Borges; Gebara, Luiza Repinaldo; Proietti, Sophia Benatti (Seven Editora, 2023)
Hyperthyroidism is defined as a thyroid dysfunction, with Graves’ disease as the most common representative. Its prevalence is 5 to 10 times higher in women. The pathology is characterized by a manifestation called thyrotoxocytosis, a clinical condition associated with the excessive production of thyroid hormones, which cause several systemic changes when in excess in the circulation. Therapeutic options consist of thionamides (Methimazole and Propylthiuracil), thyroidectomy and radioactive iodine. The present study aims to analyze, through a narrative literature review, the advantages and disadvantages of radioiodine therapy as a definitive treatment for hyperthyroidism, taking into account its indications and contraindications. Results obtained from the following databases were interpreted: LILACS-BIREME and SciELO. DOI:https://doi.org/10.56238/sevened2023.007-005